2004
DOI: 10.1002/casp.787
|View full text |Cite
|
Sign up to set email alerts
|

Eating together apart: patterns of segregation in a multi‐ethnic cafeteria

Abstract: Research on segregation has tended to focus on relations located at a macro-spatial level of analysis and unfolding in contexts where boundaries to interaction are formally established. This research, by contrast, investigated segregation as a micro-ecological process by observing patterns of seating in a multi-ethnic cafeteria. A total of 3114 seating positions were coded over a 2-week period and the resulting data were analysed using both adapted segregation indices (P and D) and loglinear and logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 31 publications
(53 reference statements)
1
76
0
Order By: Relevance
“…There was significant seating aggregation based on sex and race; people tended to sit beside others who matched themselves on these traits, which replicates findings from previous research (Campbell et al, 1966;Koen & Durrheim, in press;Clack et al, 2005). In addition, there was a weaker, but statistically significant trend for persons to sit beside others who were similar in glasses-wearing status and hair length.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…There was significant seating aggregation based on sex and race; people tended to sit beside others who matched themselves on these traits, which replicates findings from previous research (Campbell et al, 1966;Koen & Durrheim, in press;Clack et al, 2005). In addition, there was a weaker, but statistically significant trend for persons to sit beside others who were similar in glasses-wearing status and hair length.…”
Section: Discussionsupporting
confidence: 83%
“…Seating aggregation by sex has been consistently found in all the available studies on naturalistic seating arrangements (Campbell et al, 1966;Clack et al, 2005;Sriram, 2002). For this reason, sex is included in the current study to ensure that the observed location (a computer lab) is comparable to locations used in previous research, and to ensure that the statistical procedure used is sound.…”
Section: Studymentioning
confidence: 98%
See 2 more Smart Citations
“…In many cases, the local civic societies and the neighbourhood groups in the areas where this research was conducted had no members from ethnic minority backgrounds. Observational research conducted around the same time as these interviews documented a high degree of ethnic segregation among students at Manchester University (Clack et al, 2005).…”
Section: Problematizing the National Identity Problematicmentioning
confidence: 99%